Artificial Intelligence in Education : 17th International Conference, AIED 2015, Madrid, Spain, June 22-26, 2015. Proceedings - Conati, Cristina; Heffernan, Neil.; Mitrovic, Antonija; Verdejo, M. Felisa; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the refereed proceedings of the 17th International Conference on Artificial Intelligence in Education, AIED 2015, held in Madrid, Spain, in June 2015. The 50 revised full papers presented together with 3 keynotes, 79 poster presentations, 13 doctoral consortium papers, 16 workshop abstracts, and 8 interactive event papers were carefully reviewed and selected from numerous submissions. The conference provides opportunities for the cross-fertilization of approaches, techniques and ideas from the many fields that comprise AIED, including computer science, cognitive and learning sciences, education, game design, psychology, sociology, linguistics, as well as many domain-specific areas.
Is a Dialogue-Based Tutoring System that Emulates Helpful Co-constructed Relations During Human Tutoring Effective -- Educational Question Answering Motivated by Question-Specific Concept Maps -- A Study of Automatic Speech Recognition in Noisy Classroom Environments for Automated Dialog Analysis -- Teachable Agents with Intrinsic Motivation -- Temporal Generalizability of Face-Based Affect Detection in Noisy Classroom Environments -- Transfer Learning for Predictive Models in Massive Open Online Courses -- Mind the Gap: Improving Gender Equity in Game-Based Learning Environments with Learning Companions -- Comparing Representations for Learner Models in Interactive Simulations -- Games Are Better than Books: In-Situ Comparison of an Interactive Job Interview Game with Conventional Training -- Predicting Comprehension from Students Summaries -- A Tutorial Dialogue System for Real-Time Evaluation of Unsupervised Dialogue Act Classifiers: Exploring System Outcomes -- Positive Impact of Collaborative Chat Participation in an edX MOOC -- Who Needs Help? Automating Student Assessment Within Exploratory Learning Environments -- Moody Agents: Affect and Discourse During Learning in a Serious Game -- Examining the Predictive Relationship Between Personality and Emotion Traits and Learners Agent-Direct Emotions -- Evaluating Human and Automated Generation of Distractors for Diagnostic Multiple-Choice Cloze Questions to Assess Children s Reading Comprehension -- Machine Learning for Holistic Evaluation of Scientific Essays -- Learning to Diagnose a Virtual Patient: An Investigation of Cognitive Errors in Medical Problem Solving -- Studying Student Use of Self-Regulated Learning Tools in an Open-Ended Learning Environment -- Situated Pedagogical Authoring: Authoring Intelligent Tutors from a Student s Perspective -- Two Modes are Better Than One: A Multimodal Assessment Framework Integrating Student Writing and Drawing -- To Resolve or Not to Resolve? That Is the Big Question About Confusion -- Motivational Design in an Intelligent Tutoring System That Helps Students Make Good Task Selection Decisions -- SNS Messages Recommendation for Learning Motivation -- How Spacing and Variable Retrieval Practice Affect the Learning of Statistics Concepts -- Leveraging Multiple Views of Text for Automatic Question Generation -- Mind Wandering During Learning with an Intelligent Tutoring System -- Deep Stealth: Leveraging Deep Learning Models for Stealth Assessment in Game-Based Learning Environments -- Learning Mental Models of Human Cognitive Processing by Creating Cognitive Models -- A Player Model for Adaptive Gamification in Learning Environments -- Exploring the Impact of a Learning Dashboard on Student Affect -- Cognitive Tutor Use in Chile: Understanding Classroom and Lab Culture -- TARLAN: A Simulation Game to Improve Social Problem-Solving Skills of ADHD Children -- Blocking vs. Interleaving: Examining Single-Session Effects Within Middle School Math Homework -- Impact of Adaptive Educational System Behaviour on Student Motivation -- Understanding Student Success in Chemistry Using Gaze Tracking and Pupillometry -- Attentive Learner: Improving Mobile MOOC Learning via Implicit Heart Rate Tracking -- Distractor Quality Evaluation in Multiple Choice Questions -- Interpreting Freeform Equation Solving -- ITS Support for Conceptual and Perceptual Connection Making Between Multiple Graphical Representations -- Discovering Individual and Collaborative Problem-Solving Modes with Hidden Markov Models -- Improving Student Problem Solving in Narrative-Centered Learning Environments: A Modular Reinforcement Learning Framework -- Filtering of Spontaneous and Low Intensity Emotions in Educational Contexts -- Contextual Recommendation of Educational Contents -- Coherence Over Time: Understanding Day-to-Day Changes in Students Open-Ended Problem Solving Behaviors -- From Learning Companions to Testing Companions: Experience with a Teachable Agent Motivates Students Performance on Summative Tests -- Negotiation-Driven Learning -- From Heterogeneous Multisource Traces to Perceptual-Gestural Sequences: The PeTra Treatment Approach -- Probability Based Scaffolding System with Fading -- Understanding Students Use of Code-Switching in a Learning by Teaching Technology.
Keywords: Artificial intelligence; Education; Computer science; Education -- Psychology; Artificial Intelligence; Computers and Education; User Interfaces and Human Computer Interaction; Information Systems Applications (incl. Internet).; Educational Technology; Pedagogic Psychology